Android-Based Population Information System of Gunung Sugih Village as a Public Service Innovation - Puspitasari, Tuti (JLASA (Journal of Law and State Administration), 2025)
This research aims to develop an Android-based Population Data Information System for Gunung Sugih Village as an innovative solution to improve the efficiency of population administration services. The main problem faced by the village is the manual data collection process, which often leads to delays, data duplication, and recording errors. The research methodology includes system requirements analysis, system design using the waterfall model, and functional testing through the black box testing method. The results show that the developed system can manage population data in a more structured and accessible manner through mobile devices. The application provides key features such as recording births, deaths, population movements, and managing administrative documents digitally. Based on testing results, all application functions operated properly and met user needs. The implementation of this system has been proven to improve the speed of administrative services, enhance data transparency, and ensure accuracy. Therefore, the development of this Android-based information system is expected to be an initial step toward realizing modern, effective, and digitally oriented village governance that supports sustainable public service transformation